Expanding the phenotype of MED 17 mutations: Description of two new cases and review of the literature. Issue 8 (22nd October 2018) - Agostini, Annalisa; Marchetti, Daniela; Izzi, Claudia; Cocco, Isabella; Pinelli, Lorenzo; Accorsi, Patrizia; Iascone Maria, Rosaria; Giordano, Lucio
Abstract : We report the case of two siblings presenting with failure to thrive in early years, progressive microcephaly, moderate intellectual disability, developmental delay, ataxic gait and seizures with an identical EEG pattern, and minimal cerebellar atrophy. We ruled out the syndromic and metabolic causes of microcephaly and subsequently conducted a panel of genetic diagnostic tests, including the clinical exome sequencing which revealed compound heterozygous mutations in MED 17 gene in both patients. p.Glu16fs was found to be inherited from the mother and p.Gly253Arg from the father. This case along with review of the literature suggests that mutations in MED17 may define a phenotype characterized by progressive microcephaly, intellectual disability, seizures, cerebellar atrophy of variable degree, and ataxia. More cases are needed to define the phenotype–genotype correlation in MED17 mutations. However, basing on our findings, we recommend testing MED17 mutations in any patient presenting with two or more of the aforementioned signs and symptoms.